2011
DOI: 10.1007/s10661-011-1932-y
|View full text |Cite
|
Sign up to set email alerts
|

Nematode community structure in the vicinity of a metallurgical factory

Abstract: Soil nematode communities (taxa composition, trophic structure, ecological indices) in the area of metallurgical factory (Oravské ferozliatinárske závody) in Široká, Northern Slovakia were investigated in 2009. The factory belongs to main sources of emissions originated by ferroalloy production in this region. Four sites (meadows) were selected in a downwind direction from the factory: site A was located 0.85 km far from the factory, and the other sites were maintained in approximately 2-km intervals from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 39 publications
2
0
0
Order By: Relevance
“…The implicit assumption of the MI and related indices that largebodied predacious or omnivorous nematodes (with cp scores of 4-5, sometimes 3) are more sensitive and are therefore more easily lost from a system after a strong disturbance (Korthals et al, 1996;Nagy et al, 2004) does not always hold. For instance, in our study, nematodes with cp3-5 scores did not always display such sensitivity under moderate pollutant concentrations, in agreement with other recent studies (Heininger et al, 2007;Šalamún et al, 2011;Gutiérrez et al, 2016). In fact, 40% of the nematode genera, and between 25 and 40% of the abundances in our study were predators/omnivores with a cp score of 4 or 5, and this did not systematically differ between disturbed and undisturbed sites (Supplemental Material -SM 2).…”
Section: Nematode Abundance Diversity and Maturity Indicessupporting
confidence: 92%
See 1 more Smart Citation
“…The implicit assumption of the MI and related indices that largebodied predacious or omnivorous nematodes (with cp scores of 4-5, sometimes 3) are more sensitive and are therefore more easily lost from a system after a strong disturbance (Korthals et al, 1996;Nagy et al, 2004) does not always hold. For instance, in our study, nematodes with cp3-5 scores did not always display such sensitivity under moderate pollutant concentrations, in agreement with other recent studies (Heininger et al, 2007;Šalamún et al, 2011;Gutiérrez et al, 2016). In fact, 40% of the nematode genera, and between 25 and 40% of the abundances in our study were predators/omnivores with a cp score of 4 or 5, and this did not systematically differ between disturbed and undisturbed sites (Supplemental Material -SM 2).…”
Section: Nematode Abundance Diversity and Maturity Indicessupporting
confidence: 92%
“…In a mesocosm study, Šalamún et al (2015) demonstrated a positive influence of Cd and Cu, both at mg kg -1 , on sensitive nematodes (cp5) and on several nematode indices (Structure Index, MI2-5 and Shannon diversity), but values of these indices declined at still higher metal concentrations. Such positive relationships of nematodes with high cp values (sensitive taxa) to relatively low levels of metal pollution have also been reported in other field studies (Heininger et al, 2007;Šalamún et al, 2011), and this may have repercussions for the interpretation of Maturity and related indices.…”
Section: Nematode Abundance Diversity and Maturity Indicessupporting
confidence: 78%
“…Shao et al [14] concluded that nematode c-p groups 3, 4 and 5 were negatively correlated with Pb and Zn concentrations and can be utilized as indicators of heavy metal contamination. In the study by Šalamun et al [15], nematodes with the highest tolerance to elevated Mg content in soils were c-p 1 group nematodes and bacterivores. Certain nematode genera can predict specific type of disturbance.…”
Section: Introductionmentioning
confidence: 93%
“…According to Bongers [37], the species belongs to the colonizer-persister (c-p) group 1. Rhabditis was found to be tolerant to Cu, Mg and Zn [15]. Rhabditis terricola was found in the Saxon mine soil with high Pb, Zn, Fe and As contents.…”
Section: Nematode Characterizationmentioning
confidence: 98%